The Effect of Herbal Tea Consumption on the Incidence of ARI in Toddlers in the Corona Pandemic Season : Pengaruh Konsumsi Teh Herbal Terhadap Kejadian ISPA pada Anak Balita di Musim Pandemi Corona - Ruliati; Aini, Inayatul; Novitasari, Sherli (Universitas Muhammadiyah Sidoarjo, 2022)
The formation of the immune system in toddlers is not perfect, so it must be improved, especially in the pandemic season, children are vulnerable to acute respiratory infections. The purpose of the study was to determine the effect of herbal tea consumption on the incidence of ARI in children under five during the corona pandemic season in Ngumpul Village, Jogoroto, Jombang Regency. Method used posttest design, research time November 2020 to April 2021, research site in Ngumpul village, Jogoroto district, Jombang district. The independent variable is herbal tea and the dependent variable is the incidence of ARI. The population is children living in RT 06 RW 04 aged 1 to 5 years good There are 16 people who are healthy and who often get sick with coughs and colds in Ngumpul Village, Jogoroto District, Jombang Regency in 2021. Sampling technique using total sample. The Analysis using the T-Test Paired Samples The results of the study of 16 respondents before consuming herbal tea, most of them most experienced ARI as many as 11 respondents (68%). After consuming the herbal tea, most of them did not experience ARI, as many as 12 respondents (75%). The T-Test Paired Samples test obtained a significant degree value of (0.000) < (0.05) then H1 is accepted, The conclusion means that there is an effect of herbal tea consumption on the incidence of ARI in children under five in Ngumpul Village, Jogoroto District, Jombang Regency in 2021).